2013
DOI: 10.1080/00223131.2013.799397
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique ofin situphase-shift interferometry applied for faint dissolution of bulky montmorillonite in alkaline solution

Abstract: The effect of alkaline pH on the dissolution rate of bulky aggregated montmorillonite samples at 23• C was investigated for the first time by using an enhanced phase-shift interferometry technique combined with an internal refraction interferometry method developed for this study. This technique was applied to provide a molecular resolution during the optical observation of the dissolution phenomena in real time and in situ while remaining noninvasive. A theoretical normal resolution limit of this technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The observed rate difference might be related to ambient conditions such as the pH or the amounts of aqueous SiO 2 and Ca 2+ surrounding the silica spheres. Similar observations have been performed by interferometry on dissolving calcite in pure water in the presence and absence of flow . However, calcite does not swell and simply undergoes formation of etch pits under these conditions.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The observed rate difference might be related to ambient conditions such as the pH or the amounts of aqueous SiO 2 and Ca 2+ surrounding the silica spheres. Similar observations have been performed by interferometry on dissolving calcite in pure water in the presence and absence of flow . However, calcite does not swell and simply undergoes formation of etch pits under these conditions.…”
Section: Resultssupporting
confidence: 76%
“…Similar observations have been performed by interferometry on dissolving calcite in pure water in the presence and absence of flow. 14 However, calcite does not swell and simply undergoes formation of etch pits under these conditions. In situ TEM observations detected both expansion, as a result of diffusion of water into the solid through hydration, and void formation through release of solute into water through dissolution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Phase-shift interferometry provides nanoscale resolved measurements of ultra-slow growth and dissolution of minerals (e.g., van Driessche et al 2011) with a detection limit of <10 -5 nm/s, depending on the stability of the machine, light wavelength and refractive index of the solution or mineral (e.g., Ueta et al 2013). This technique has the benefit of a larger lateral area of study than that of other in situ experimental methods such as atomic force microscopy (AFM) and can be used to obtain long-term measurements of dissolution and growth (see e.g., Green and Lüttge 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Refractive index (86) Concentration (104) Growth or dissolution (74)(75)(76) Growth or dissolution (77) Diffusion coefficient (62) used a Fizeau interferometer with a laser as light source to investigate the film thickness of a liquid wetting the wall of a rectangular microchannel when the channel is emptied. Their results confirmed that a model applied to circular tubes (63) can also be applied to rectangular channels in order to describe the layer thickness during outflow.…”
Section: Total Internal Reflectionmentioning
confidence: 99%